Geographical patterns of implementing a government subsidy program: implications for health outcomes and nutrient intake in Iran - Pakravan-Charvadeh, Mohammad Reza (Frontiers in Public Health, 2024)
The lack of access to a diverse and nutritious diet has significant health consequences worldwide.Governments have employed various policy mechanisms to ensure access, but their success varies. In this study, the impact of changes in food assistance policy on food prices and nutrient security in different provinces of Iran, a sanctioned country, was investigated using statistical and econometric models. Both the old and new policies were broad in scope, providing subsidized food or cash payments to the entire population. However, the implementation of these policies led to an increase in the market price of food items, resulting in a decline in the intake of essential nutrients. Particularly, the policy that shifted food assistance from commodity subsidies to direct cash payments reduced the price sensitivity of consumers. Consequently, the intake of key nutrients such as Vitamin C and Vitamin A, which are often constrained by their high prices, decreased. To improve the diets of marginalized populations, it is more effective to target subsidies towards specific nutrient groups and disadvantaged populations, with a particular focus on food groups that provide essential nutrients like Vitamin A and Vitamin C in rural areas of Iran. More targeted food assistance policies, tailored to the specific context of each province and income levels, are more likely to yield positive nutritional outcomes with minimal impact on food prices.